PENGARUH PANDEMI COVID–19 TERHADAP PELAKSANAAN KONTRAK PENGADAAN BARANG DAN JASA - Ariwibowo Dwi Rahmanto; Yasarman (The Juris, 2022)
Countries in the world are now faced with the great challenge of handling the coronavirus outbreak which is officially identified by the World Health Organizations (WHO) as Corona Virus Desease-19. The impact of the Covid-19 outbreak is not only detrimental to health but also affects the economies of countries around the world, including Indonesia. or Covid-19 for short. Business actors, both large and medium scale, have now begun to accommodate. Many companies closed their businesses and factories due to the decline in trade transactions due to lack of buyers and limited exports. In this discussion, it raises problems, namely: How the Covid-19 pandemic affects the Goods/Services Procurement contract and how to position the parties in the goods and services procurement contract related to default. The effect of the Covid-19 pandemic on the procurement contract for goods and services must be seen based on the status of the goods and services procurement contract itself whether it has been implemented or is it still in the initial process. For government goods and services procurement contracts that have been implemented, clauses related to Force Majeure are regulated in Presidential Regulation No.16/2018 concerning Government Procurement of Goods/Services.